PERANCANGAN APLIKASI AUGMENTED REALITY RUKUN ISLAM DENGAN PENDEKATAN OBJECT ORIENTED ANALYSIS & DESIGN (OOAD) - Kartika Wahyuningsih; Arviansyah, Muhammad Busthomi; Syach, Muhammad Ferdyan (Systemic: Information System and Informatics Journal, 2025)
The pillars of Islam are an important foundation for Muslims. One of the problems often experienced by early childhood in learning religious lessons, especially the pillars of Islam, is the difficulty of understanding by memorizing methods found in books or on the internet. In addition, the method of memorizing each sequence in the pillars of Islam is less effective because children will easily forget the memorized sequence. So in this study will design an AR application for the introduction of the pillars of Islam. In addition, this research will use the Object Oriented Analysis and Design (OOAD) model approach. The AR application of the pillars of Islam was successfully built using unity and tested using blackbox testing and UAT. The results of blackbox testing get results that are in accordance with the existing scenario. While the results of testing using UAT produced a percentage of 92.2% in the "Very Feasible" category.